Kitchen lamps as a cause of mortality for urban insects (UNED Research Journal, 2018)
Fluorescent lamps in kitchens accumulate grease from cooking oil fumes and become traps for insects, particularly dipterans. New smaller lamps may be less harmful for urban insect populations.
Keywords: mortality of urban insects; harmful cooking oil fumes; insects in cities